Bioengineered hyaluronan hydrogels for the delivery of molecular and cellular therapies - Silva, J (2023)
Hyaluronan (HA) is an extracellular matrix (ECM)-based polymer with unique physicochemical properties including biocompatibility, biodegradability, viscoelasticity, and high-water retention. However, its solubility in water drastically reduces its half-life in vivo. Through judicious chemical modifications, its structure is easily crosslinked and can conjugate with numerous therapeutic molecules, extending their therapeutic function. Throughout this review, an overview of crosslinking methods to create HA hydrogels is provided, including covalent (permanent, transient/dynamic) and non-covalent chemistries, as well as the use of non-modified HA in supramolecular hydrogels. HA-based injectable hydrogels are very appealing as a three-dimensional network for the delivery of therapeutic molecules (drugs and biomolecules) and stem cells. HA hydrogels are capable of mimicking important features of the native ECM and can provide spatiotemporal signals to regulate cell fate. The final part of the review also describes the application of HA hydrogels as vehicles for delivering stem cells and therapeutics, capable of modulating cell behavior.